Assistance of the Tanah Abang Traders Association (HIPTA) in dealing with the Covid-19 Pandemic - Ida Busnetty; Dian Octaviani; Husna Leila Yusran; Safnita Safnita (Universitas Muhammadiyah Magelang, 2021)
The prolonged crisis due to the Covid-19 pandemic that hit Indonesia had a significant impact on various sectors, including the goods and services trade sector. Traders in the wholesale center of textiles and textile products in Tanah Abang are one of the parties who really feel the impact. The declining purchasing power of the people coupled with the necessity to close shops during the Implementation of community activity restrictions led to a decrease in income, while the obligation to pay operational costs still had to be carried out. This forced quite a number of traders to decide to close their businesses. The purpose of this activity is to find the best solution for the business continuity of traders. The method used is the focus group discussion. The conclusion obtained is the need for the application of digital marketing at the Tanah Abang wholesale center. The steps that need to be taken are socializing about the importance of digital marketing, training on social media creation and creating a market place or website that provides marketing access for all traders.